Toxoplasmosis associated with digital vasculitis and immunodeficiency–a dilemma in diagnosis. Issue 707 (September 1984) - Ellis, M. E.; Webb, A. K.; Dunbar, E. M.
Abstract : We present a case of acquired toxoplasmosis associated with severe digital vasculitis–a previously unreported finding. The rise in Toxoplasma gondii antibody titres may have been attenuated by impaired cellular immunity, and this poses a problem for diagnosis.